The Dynamics of Social Assistance Benefit Receipt in Germany State Dependence Before and After the Hartz Reforms - Königs, Sebastian (OECD Social, Employment and Migration Working Papers, 2013)
In this paper, we study the dynamics of social assistance benefit receipt in Germany using annual survey data from the German Socio-Economic Panel (SOEP) for the years 1995-2011. Rates of benefit receipt were stable in Germany at around 8% in the 1990s but started rising in 2001 to peak at over 12% in 2006. We show that this increase in the receipt rate can be attributed to lower exit rates from benefit receipt since 2001. In the econometric part of the paper, we study state dependence in social assistance benefit receipt, i.e. the question to what extent benefit receipt today predicts the probability of future benefit receipt. We estimate a series of dynamic random-effects probit models that control for unobserved heterogeneity and endogeneity of the initial conditions and indeed find considerable evidence of state dependence. Our estimates suggest that benefit receipt one year ago raises the likelihood of benefit receipt today by a factor of 3, which corresponds to an average partial effect of about 14 percentage points. The level of state dependence differs between subsamples and is larger in absolute terms for women, Eastern German residents, and migrants, for whom receipt rates are higher. Studying variations over time, we find a rise in the level of state dependence after the 2005 Hartz reforms in Eastern Germany. We attribute this effect to a drop in average predicted entry rates into benefit receipt without a corresponding fall in predicted benefit persistence rates. We do not identify any comparable change in structural dependence for Germany as a whole or other subsamples we look at. Since a reform that contributes to keeping individuals off benefits while doing little to raise exit rates would increase state dependence but might nonetheless be considered as beneficial, our findings should not be understood as a verdict on the success or failure of the Hartz reforms